Identification of four-jointed box 1 as a potential oncogene in nasopharyngeal carcinoma / Muhammad Mamduh bin Ahmad Zabidi - Ahmad Zabidi, Muhammad Mamduh (2011)
Nasopharyngeal carcinoma (NPC) is a highly metastatic cancer that is endemic in South East Asia and Southern China. Despite the gravity of the disease, the current knowledge on its molecular pathogenesis is still inadequate to improve the disease management. The present study seeks to understand the molecular mechanism of NPC, with an aim to identify potential therapeutic targets or biomarkers. From a previous expression microarray study, Four – Jointed Box 1 (FJX1) gene was found to be upregulated in NPC compared to non-cancerous controls with negligible expression in 5 vital normal human organs. Human FJX1 is a Drosophila orthologue of four-jointed (fj) gene which codes for a Golgi-resident kinase that phosphorylates specific cadherin domains and functions downstream of the Notch and Hippo signaling pathways. The overexpression of FJX1 in primary NPC tissues was confirmed at both mRNA and protein levels, while its low expression was validated in 16 normal human organs. Both overexpression and knockdown experiments showed that FJX1 increased the aggressiveness of NPC cells by promoting cell proliferation, invasion and anchorageindependent growth. Concomitant change of Cyclins D1 and E1 levels were observed with FJX1 level, suggesting FJX1 enhances cell proliferation through cell cycle regulation. The results of the present study demonstrate for the first time the overexpression of FJX1 in NPC as a putative oncogene, and it represents an attractive therapeutic target for NPC.